Meta-analysis of the Effect of STEM-Based Integrated Science E-books on Students' Scientific Literacy - Asrizal Asrizal; Fleony Dea Amanda; Endang Aldilla; Jufiani Ulfa (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2023)
This research aims to accomplish three things. first, to see how much influence is exerted by the use of STEM-based integrated science e-books in terms of education level. Second, to determine its magnitude is exerted by the use of STEM-based integrated science E-books in terms of the teaching model. Third, to determine the extent of use's impact of STEM-based integrated Science E-Books has on students' scientific literacy. Meta-analysis research is the method used which aims to review several past studies using a quantitative approach. Based on the learning material that was carried out with heterogeneity tests, only three subjects had different populations, namely impulse and momentum material, vibration and waves, and environmental pollution, the results obtained were Q > df so that the hypothesis test obtained from the results of p < a in three H0 subjects was rejected . Based on the level of education with heterogeneity tests, namely junior high and high school, the value of Q> df was obtained so that the hypothesis test for elementary, junior high and high school p> a H0 was accepted and PT p <a H0 was rejected. Based on scientific literacy testing of heterogeneity obtained Q > df and using hypothesis testing the value of p < a H0 is rejected. The Integrated Science E-book has an effect on students' scientific literacy skills, according to the analyzed data.